Investigaciones sobre Dermatitis Esquistosómica en el Lago de Pátzcuaro, Michoacán, México - Caballero y C., Eduardo; Flores-Barroeta, Luis; Hidalgo E., E. (Revista de Biología Tropical, 1961)
Two series of collections in Lake Patzcuaro, Michoacan, Mexico, made with the purpose of investigating the presence of schistosome - dermatitis (swimmer’s itch) have yielded negative results in the snails collected-Physa mexicana tolucensis, Helisoma tenuis boucardi, Sphaerium triangularis and S. subtransversum. A new distome, leptocercous, gymnocephalous cercaria was obtained from Physa mexicana tolucensis, and described here as Cercaria patzcuarensis n. sp.